Ministry Of Finance Decree No. 426 Of The Year 2016 Amending Certain Provisions of the Executive Regulations of the Tenders and Bids law promulgated by Decree No. 1367 of the year 1998 = وزارة المالية قرار رقم 426 لسنة 2016 بتعديل بعض أحكام اللائحة التنفيذية لقانون تنظيم المناقصات والمزايدات الصادرة بالقرار رقم 1367 لسنة 1998 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic